Manajemen Kepemimpinan Pengasuh Pesantren Dalam Meningkatkan Sumber Daya Manusia Dan Daya Saing Pondok Pesantren (Studi Di Pondok Pesantren Salman Al-Farisi Di Desa Gayam, Kabupaten Kediri) - Yusron Mustofa, Mochammad; Sustiyatik, Enni; Utami, Sasi; Rahayu, Budi (Jurnal Ilmiah Raflesia Akuntansi, 2023)
This study aims to examine the leadership management of the caretakers at the Salman Al-Farisi Islamic Boarding School in Gayam Village, Kediri Regency, in enhancing the quality of human resources and the competitiveness of the boarding school. The purposive sampling technique was used for sample selection, and a total of 5 individuals were chosen as samples. The analysis techniques used include reduction analysis, display analysis, and conclusion drawing. The results of this study are: 1) The leadership management of the boarding school caretakers in improving human resources and competitiveness involves participating in various activities, which significantly enhance human resources. 2) The supporting factors for improving the quality of human resources and the competitiveness of the Salman Al-Farisi Islamic Boarding School include implementing the vision and mission of the school, which serves as a supportive factor in enhancing human resources and competitiveness. The leadership at the school is not authoritarian, and the school leader provides opportunities for staff and teachers to engage in learning activities outside the school. Additionally, human resources that align with their fields can improve quality and compete with other Islamic boarding schools. The inhibiting factor comes from the lack of budget to support all programs, necessitating collaboration with donors.